Music Micro form (2015)
Our object of study, in this case, was located (2009) within the subject known as Musical Forms, Morphology or Shape Analysis, whose study of the smallest structural parts or fragments we can call "Micromorphology". Our review of it started from understanding it as that musicological discipline that is carried out at the immanent level, on the written musical score or text and we judge it as relevant (past) for the following reasons: subsection, phrase, period, figure, group of phrases or section and their applications to musical texts, in some writers, often present confusion, divergence and even contradictions; b) no mention is usually made of those segments of a work that are of lower rank or centrality and attention is usually focused on those with thematic hierarchy (protagonist, complementary or antagonistic). We rely, on that inquiry, that, conceptually, it seemed clearer to consider the durations or sizes of the segments or phrases and their commensurability, their mutual hierarchical relationships, their harmonic base and their modes of union, separately from the thematic aspects, without ignore the structuring functions of these in the musical piece.